Investigating the Effects of Cloud-Based Business Intelligence Adoption on Services Delivery Quality and Customers Participation in Private Sector Companies in UAE - ELSHABOURI, MOHAMED IBRAHIM HAMZAWI (2023)
Purpose: This dissertation aims to investigate the effects of cloud-based business intelligence (BI) adoption on service delivery quality and customer participation in private sector companies in the United Arab Emirates (UAE). The study seeks to address the research gap regarding the specific impacts of cloud-based BI in the UAE context and provide practical insights for organizations striving to improve operations and enhance customer experiences. Methodology: A mixed methods approach will be employed to collect quantitative and qualitative data from a sample of private sector companies in the UAE. The study will focus on two key areas: the impact of cloud-based BI adoption on service delivery quality and its influence on customer participation. The data will be gathered through interviews and surveys, allowing for a comprehensive analysis of the research questions. Findings: The findings from this study will shed light on the effects of cloud-based BI adoption on service delivery quality and customer participation in private sector companies in the UAE. The study will provide empirical evidence and insights into the specific benefits and challenges associated with adopting cloud-based BI in the UAE context. Implications: The results of this study will have practical implications for private sector companies in the UAE seeking to enhance their operations and improve customer experiences through cloud-based BI adoption. The findings will inform strategic decision-making processes and provide guidance for organizations looking to optimize service delivery quality and customer engagement. Originality/Value: This research contributes to the existing body of literature by addressing the research gap in understanding the effects of cloud-based BI adoption on service delivery quality and customer participation in private sector companies in the UAE. The study provides original insights and empirical evidence specific to the UAE context, offering valuable contributions to the field of cloud-based BI implementation and its impacts on organizational performance and customer engagement.